Innovative Governance in Public Services Management Through the Jakarta Kini Application in DKI Jakarta Province (Jurnal Bina Praja, 2024)
One of the concepts of Jakarta Smart City is marked by the existence of regional innovation. The JAKI (Jakarta Kini) application is a one-stop service innovation that helps people with their daily activities. Management of the JAKI (Jakarta Kini) application as a regional innovation aligns with innovative governance in public administration studies. Innovative governance as a renewal of good governance is not enough to overcome problems, especially in the public sector. The study aims to analyze the implementation of Innovative Governance in Managing Public Services through the JAKI (Jakarta Kini) Application in DKI Jakarta Province and to find out Innovative Governance in Managing Public Services Through the JAKI (Jakarta Kini) Application in DKI Jakarta Province. The study used qualitative research methods. Primary data sources were obtained from interviews, and secondary data from books, articles, and previous research. The data analysis technique uses the Miles and Huberman model. This study analyzed innovative governance as public service management through the JAKI (Jakarta Kini) application in DKI Jakarta. The results showed that government governance in DKI Jakarta can be categorized as innovative through the JAKI (Jakarta Kini) application. However, the management must carry out active outreach to increase community participation and make regular improvements to minimize errors in the service system.
Keywords: Public Service; Innovation; Governance